2016
DOI: 10.1007/s00402-016-2536-3
|View full text |Cite
|
Sign up to set email alerts
|

Significant differences in femoral torsion values depending on the CT measurement technique

Abstract: IntroductionThis study compared the feasibility of six different CT-based measurement techniques for establishing an indication for derotational osteotomy in the cases of patellar instability or femoral fracture.Materials and methodsCT scans of 52 single human cadaver femora were measured using six different torsion measurement techniques (described by Waidelich, Murphy, and Yoshioka on transverse images and Hernandez, Jarrett, and Yoshioka on oblique images). All measurements were performed by four observers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
124
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 27 publications
8
124
1
1
Order By: Relevance
“…In addition to measuring total torsion, segmental femoral torsion was determined for the proximal metaphysis, the diaphysis, and the distal metaphysis separately. In agreement with the literature we found almost perfect intra-and inter-rater agreement for total femoral torsion measurements [15]. By calculating the ICC we were able to show that the measurement protocol introduced is a reliable tool for evaluation of segmental torsion, as we found substantial to almost perfect intra-and interobserver agreement for all parameters.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition to measuring total torsion, segmental femoral torsion was determined for the proximal metaphysis, the diaphysis, and the distal metaphysis separately. In agreement with the literature we found almost perfect intra-and inter-rater agreement for total femoral torsion measurements [15]. By calculating the ICC we were able to show that the measurement protocol introduced is a reliable tool for evaluation of segmental torsion, as we found substantial to almost perfect intra-and interobserver agreement for all parameters.…”
Section: Discussionsupporting
confidence: 89%
“…However, their data were based only on measurements in MRI [10]. The reliability of total torsion measurement in CT was evaluated in previous studies, and it was reported that depending on the method used significant differences in torsion measurements and their reliability can be found [15,18]. Recently, Kaiser et al reported that total femoral torsion measurements can differ by more than 10°, depending on the measurement technique used [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method has been recorded on more than 500 limbs 92 with mean internal femoral torsion of 24.1 AE 17.4 degrees and mean external tibial torsion of 34.9 AE 15.9 degrees. Findings which were confirmed by Kaiser et al 93 in their study comparing six methods to measure femoral torsion, all with high reliability. Liodakis et al 94 identified sufficient variation in the values yielded from different methods to preclude direct comparison.…”
Section: Axial Planesupporting
confidence: 63%